Designing an Interactive Virtual Laboratory Learning Experience for Acid-Base Indicators - Putra, Abrar Suryadi; Zainul, Rahadian (Orbital: Jurnal Pendidikan Kimia, 2024)
Science education, especially chemistry, plays a vital role in the development of conceptual understanding and practical skills among students. In the modern digital era, the integration of technology into education is indispensable to meet the demands of modern curricula. Virtual laboratories provide a safe and efficient way of teaching chemical concepts without the hazards that come with physical laboratories. This research was conducted to design, validate, and determine the feasibility of interactive virtual laboratory learning media for acid-base indicators. This research used the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. There were 79 Phase F high school students, and seven expert validators involved in the research, comprising chemistry lecturers and teachers. The data collection used questionnaires and interviews, while the validation used Aiken's index. The results showed that the virtual laboratory achieved high validity scores across content, construct, and technical quality, ranging from 0.76 to 0.90. The results indicated that the interactive virtual lab significantly enhanced the students' visualization of abstract chemical concepts, thus improving their engagement and understanding. This illustrates the potential of integrating technology into chemistry education to create more effective and engaging learning experiences.